Abortion as Essential Health Care and the Critical Role Your Practice Can Play in Protecting Abortion Access. Issue 5 (10th November 2022) - Fay, Kathryn E.; Diouf, Khady; Butler, Sharlay K.; Onwuzurike, Chiamaka; Wilkinson, Barbara E.; Johnson, Natasha R.; Schantz-Dunn, Julianna; Bartz, Deborah
Abstract : Obstetrician–gynecologists have both the skills and the knowledge to incorporate abortion into their clinical practices, and our patients deserve a specialty-wide concerted effort to deliver comprehensive reproductive health care at this critical moment. Abstract : Few obstetrician–gynecologists (ob-gyns) provide abortion care, resulting in abortion being separated from other reproductive health care. This segregation of services disrupts the ob-gyn patient–clinician relationship, generates needless costs, delays access to abortion care, and contributes to stigma. General ob-gyns have both the skills and the knowledge to incorporate abortion into their clinical practices. In this way, they can actively contribute to the protection of abortion access now with the loss of federal protection for abortion under Roe v Wade . For those who live where abortion remains legal, now is the time to start providing abortions and enhancing your abortion-referral process. For all, regardless of state legislation, ob-gyns must be leaders in advocacy by facilitating abortion care—across state lines, using telehealth, or with self-managed abortion—and avoiding any contribution to the criminalization of those who seek or obtain essential abortion care. Our patients deserve a specialty-wide concerted effort to deliver comprehensive reproductive health care to the fullest extent.